Measurements of the proton-induced reaction cross-sections of Mo-nat by using the MC50 cyclotron at the Korea Institute of Radiological and Medical Sciences - Khandaker, Mayeen Uddin; Kim, G.; Meaze, A.; Kim, K.; Son, D. (2006)
We measured the production cross-sections of Tc-99m, Tc96(m+g), Tc-95m, and Tc-95g radioisotopes for proton-induced reactions on molybdenum by using a stacked-foil activation technique in the energy range of 10-30 MeV at the MC50 cyclotron of the Korea Institute of Radiological and Medical Sciences. Reactions induced on the aluminum and copper foils were used to monitor the parameters of the proton beam. The present measurements are in generally good agreement with the earlier reported data in the investigated energy region.